Accelerate the Transition to International Financial Reporting Standards - Mardanov Zafar Khurramovich (Genius Publishing Group, 2023)
The article contains opinions on the nature of international financial reporting standards (IFRS), ongoing work to ensure the implementation of PD-4611, and modern methods of teaching international financial reporting standards.
Keywords: financial accounting and reporting; international standards of financial reporting; national accounting standards.